Moreuil Church in 1915 - Auteur inconnu (Wikimedia Commons, 1915)
Carte postale ancienne issue de Wikimedia Commons. Titre: Moreuil Church in 1915. The church in Moreuil, France, seen on a 1915 postcard. The church was largely destroyed in the First World War and has since been rebuilt
Droits : Licence Public domain via Wikimedia Commons
Keywords: carte postale; image; Patrimoine; Histoire Locale; Wikimedia Commons; église; Carte postale